The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/eye.2016.296
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic variation in primary idiopathic macular hole surgery

Abstract: PurposeThe purpose of the study was to investigate the role of ethnicity on idiopathic macular holes (IMH) structure and surgical outcome. This was a retrospective review.Patients and methodsConsecutive patients undergoing primary IMH surgery at two surgical sites of Moorfields Eye Hospital (London, UK) between April 2012 and June 2013. The main outcome measure was post surgical anatomical closure of IMH.ResultsTwo hundred and twenty two primary IMH surgeries were undertaken. A standard procedure including par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Furthermore, a variety of different adjunctive procedures are often used to augment full-thickness macular hole (FTMH) closure; examples include repeat fluid-gas exchange with or without extending the extent of the ILM peel, radial nerve fibre layer (NFL) incisions, ILM flaps, retinal massage, autologous platelets, and microdrain procedures. 5,6 The relative effects of these adjunctive techniques are disputed with some concerns that successful closure is not always accompanied by improvement in vision.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a variety of different adjunctive procedures are often used to augment full-thickness macular hole (FTMH) closure; examples include repeat fluid-gas exchange with or without extending the extent of the ILM peel, radial nerve fibre layer (NFL) incisions, ILM flaps, retinal massage, autologous platelets, and microdrain procedures. 5,6 The relative effects of these adjunctive techniques are disputed with some concerns that successful closure is not always accompanied by improvement in vision.…”
mentioning
confidence: 99%
“…Risk factors affecting primary closure, such as age, hole size, hole duration, myopia, internal limiting membrane (ILM) peeling, and preoperative visual acuity [1][2][3][4] are established, and outcomes are frequently positive with reported closure rates of 85% to 96%. 2,5,6 However, despite the high success rate of primary surgery, nonclosure does occur and factors affecting the outcome of revision surgery are less established. Previous articles, including a recent meta-analysis, 7 have investigated success rates in revision surgery, yet the visual benefits are unclear, with patients grouped categorically into gains of greater or less than 10 letters.…”
mentioning
confidence: 99%
“…In addition, the follow-up duration of 10 months may not be sufficient to fully observe the evolution of glial proliferation because in this study the significant resolution of the glial proliferation was identified in only one-half of the eyes. Moreover, the ethnic variation is an independent factor associated with the surgical prognosis [22, 23]. As a result, the findings of this study might not be reproducible with other ethnicities.…”
Section: Discussionmentioning
confidence: 83%
“…According to two US research and two UK studies, people of African descent tend to have bigger IFTMH sizes than people of Caucasian ancestry, which may be related in part to their delayed presentation, and longer wait times for surgery. [ 13 , 14 , 15 , 16 ]…”
Section: Methodsmentioning
confidence: 99%